Persepsi Wisatawan Tentang Daya Tarik Wisata Danau Kerinci - Aini Wirya; lise asnur (Departemen Pariwisata Universitas Negeri Padang, 2022)
The background of this research is the observation of Lake Kerinci and several negative reviews of tourists about Lake Kerinci found on google reviews, such as fish cages in Lake Kerinci which were established freely and uncontrollably, causing the natural scenery of Lake Kerinci to be disturbed and polluted, accessibility difficulties for tourists who using public transportation, water shortages in public toilets, causing the cleanliness of the toilets to not be maintained, there are still illegal collection activities (Pungli), and the number of trash bins is still small and inadequate, causing a lot of garbage to be scattered along with the absence of cleaners. This research aims to find out what tourists think about the tourist attraction of Lake Kerinci which is reviewed using indicators: attraction, accessibility, amenities and ancillary service. This research is a quantitative descriptive research, The research sample amounted to 82 people from 428 population and used accidental sampling technique. The data was obtained by distributing a structured questionnaire using a Likert Scale. Data analysis used descriptive analysis to categorize respondents' answers. The results of the study stated that the perception of tourists about the tourist attraction of Lake Kerinci is categorized as bad with a percentage of 40%. (1) Based on the attraction indicator, it is categorized as bad with a percentage of 54%. (2) Based on the indicators of accessibility (accessibility) is categorized as sufficient with a percentage of 67%. (3) Based on the indicators of amenities (facilities) are categorized as bad with a percentage of 42%. (4) based on the ancillary service indicator (supporting facilities) it is categorized as bad with a percentage of 34%.